Implementasi Pendidikan Karakter Di SMP Negeri 12 Kota Cirebon - Rehna Intan Fitriyani; Nuryana Nuryana; Yunita Yunita (STKIP ROKANIA, 2022)
This study aims to describe the implementation achievements of character education programs in classroom, extracurricular and out-of-class habituation at SMP Negeri 12 Cirebon City. This study uses the application of character education in schools because teachers are not paying attention to students at this time. The method used in this research is descriptive. Data collection is using interviews, observations, and document studies. Data analysis techniques used in this research are data reduction, data presentation, and conclusion drawing. Sources of data were obtained from school principals, homeroom teachers, educators/teachers, students in grades VII, VIII, and IX as well as representatives of guardians of students from grades VIII and IX. The results of the study indicate that the character education program has achieved very good results implemented by school residents and has implemented character values ​​in schools. Judging from the implementation of character education programs, these advantages and obstacles achieve maximum results in implementing character education programs. Overall the character education program has met the standard criteria, but there are several focuses that need to be improved including, 1) the principal to make a decree for the team implementing character education tasks, 2) teachers to further improve the application of character values ​​in school daily activities, 3) Students carry out character education programs held in schools well and participate actively, 4) Parents give special attention to their children by educating through habituation of good attitudes and behavior in everyday life.